Destilasi-Dehidrasi Bioetanol dari Nira Aren dan Karakteristiknya - A. LAY; P. M. PASANG; TEUKU A. IQBAL (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
Destilation-Dehidration of Bioethanol from Sugar Palm Sap and its CharacteristicsThe experiment was conducted in Engineering Repair of Indonesia Coconut and Other Palmae Research Institute, during August to December 2009. The research used observation methods of destilllation and dehydration process of bioethanol. Treatments consisted of condition of raw material of ethanol with varying characteristics. Twenty five samples were analyzed in this study. Destillation and dehydration process of bioethanol was used continuous system. Observation included the characteristics of distillation temperature, characteristics of bioetanol before and after processing, and material balance of bioetahnol. Analysis of data using multiple regression with OLS (Ordinary leas squares) method. The results showed that characteristics of bioethanol with high ethanol content, contain high sugar content and neutral acidity solution. Where as the low ethanol content , contain low sugar levels and high acidity solution. In the distillation-dehydration process of bioethanol with temprature controlled will increase the ethanol content, sugar content and pH of bioethanol. Bioethanol with 95-96 % ethanol content, sugar content of 18.0 to 18.5 % and pH 7.0-7.38. Bioethanol with contont 30.0 to 35.0, destlled and sehydrated could produce beoethnol content of 95.0-96.0 as much as 29.1 %.